ANALISIS MODEL PEMBELAJARAN PROBLEM BASED LEARNING MELALUI MEDIA TEKA-TEKI SILANG PADA PEMBELAJARAN IPAS BAB 5 DI KELAS IV SD - Rio Adi Syahputra; Anggit Grahito Wicaksono; Elinda Rizkasari (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2025)
This study was conducted to examine the implementation of the Problem Based Learning (PBL) model combined with crossword puzzle media in teaching Natural and Social Sciences (IPAS) Chapter 5 for fourth-grade students at SD Negeri 3 Mangunrejo. The main purpose of this research is to explore how the PBL model is applied through this medium, the challenges encountered during its implementation, as well as the strengths and weaknesses experienced by both teachers and students. A qualitative descriptive approach was employed, with the subjects consisting of the principal, teachers, and students, while the research object was SD Negeri 3 Mangunrejo. Data were collected through interviews, observations, and documentation, with validity tested using triangulation of techniques and sources. Data analysis followed Miles and Huberman’s stages, including data collection, reduction, display, and conclusion drawing. The findings reveal that the application of PBL supported by crossword puzzles can enhance students’ participation and enthusiasm in the learning process. Nevertheless, teachers still face certain obstacles, such as limited instructional time and difficulties among some students in understanding the given tasks. The advantages of this method include improved interaction, critical thinking skills, and a more enjoyable learning atmosphere, while its weaknesses lie in varying levels of student comprehension that require teachers to adopt specific strategies.